2019
DOI: 10.1245/s10434-019-07825-7
|View full text |Cite
|
Sign up to set email alerts
|

The MELFO Study: A Multicenter, Prospective, Randomized Clinical Trial on the Effects of a Reduced Stage-Adjusted Follow-Up Schedule on Cutaneous Melanoma IB–IIC Patients—Results After 3 Years

Abstract: Background This study compares well-being, recurrences, and deaths of early-stage cutaneous melanoma patients in follow-up, as recommended in the Dutch guideline, with that of patients in a stage-adjusted reduced follow-up schedule, 3 years after diagnosis, as well as costs. Methods Overall, 180 eligible pathological American Joint Committee on Cancer (AJCC) stage IB–IIC, sentinel node staged, melanoma patients (response rate = 87%, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 29 publications
2
43
0
Order By: Relevance
“…These results mirror the findings of the Dutch group, which recently reported very similar results in 2019. 18 As in the Dutch study, our data indicated that the large majority of patients were satisfied with their follow-up regimen regardless of the schedule. The data suggest that patients undergo a period of adjustment during the first 12 months of the follow-up period after treatment before they settle into the follow-up routine.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…These results mirror the findings of the Dutch group, which recently reported very similar results in 2019. 18 As in the Dutch study, our data indicated that the large majority of patients were satisfied with their follow-up regimen regardless of the schedule. The data suggest that patients undergo a period of adjustment during the first 12 months of the follow-up period after treatment before they settle into the follow-up routine.…”
Section: Discussionsupporting
confidence: 72%
“…The interim results of this phase 3 RCT at 3 years, undertaken in a native English-speaking cohort, appear to have validated the findings of our Dutch colleagues who undertook this study in the Netherlands using the same protocol. 18 The UK MelFO study seems to support the notion that a reduced stage-adjusted follow-up schedule is an appropriate and safe approach for AJCC stages 1B to 2C melanoma patients after staging with sentinel biopsy in terms of QoL, patient satisfaction, and disease safety at 3 years. We anticipate reporting the final outcome of the study at the end of 2020, with the data from the Netherlands and the UK combined to ensure adequate power to detect any difference in recurrence rates, thereby dispelling any lingering concerns about patient safety with a reduced follow-up regimen.…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…The current randomized controlled MELFO study compared two groups of stage Ib-IIc melanoma patients, 3 years after diagnosis. 5 The first group received follow-up as advised in the guideline, while the second group received a stage-adjusted, less frequent follow-up schedule. Patients' QoL, anxiety, satisfaction regarding follow-up, and disease-free and overall survival were comparable, but a 39% cost reduction was found in those who were less frequently followed-up.…”
Section: Presentmentioning
confidence: 99%